Manajemen sumber daya manusia berbasis nilai-nilai Islami: Analisis MSDM di pesantren salafiyah Asshoghiri Rejang Lebong - Pratama, Rediansyah; Taufiqurrahman, Taufiqurrahman; Novaldo, Sandi; Yulita, Ona; Anwar, Khairul (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2025)
Islamic boarding schools as Islamic educational institutions require human resource management (HRM) that is in line with Islamic values. This study analyzes Islamic value-based HRM at the Salafiyah Asshoghiri Islamic Boarding School, focusing on the role of HR, challenges, planning, and evaluation. Using a qualitative case study approach, data were collected through interviews, observations, and documentation studies. The results of the study show that HR management at this Islamic boarding school is centered on the values of Honesty–Prayer–Fear of the Forbidden, which form the basis for recruitment, training, and supervision. The main challenges include character incompatibility, variations in discipline, and environmental influences. HR planning is carried out selectively and value-oriented, while continuous evaluation integrates behavioral observation and moral consistency. This model offers an effective approach to character building and institutional strengthening based on Islamic values.